PENGARUH PENGALAMAN PELANGGAN DAN KUALITAS LAYANAN TERHADAP MINT BELI ULANG PADA PRODUK KOREAN FOOD DI MTV KOTA PASURUAN - Anggreani, Zahrotul Ikhda; Akramiah, Nurul; Erwantiningsih, Eni (Yayasan Education and Social Center, 2025)
The development of Korean culture in Indonesia increases public interest in Korean Food products. MTV K-Mart Pasuruan is present as a typical Korean retail store that offers a unique shopping experience. This study aims to determine the effect of customer experience and service quality on repurchase interest in Korean Food products at MTV K-Mart Pasuruan City. Respondents in this study were 70 MTV K-Mart consumers using the purposive sampling method, and data analysis was carried out using multiple linear regression tests. The results of the study showed that simultaneously, customer experience and service quality had a significant effect on repurchase interest, with a calculated F value of 24.750> F table 3.13 and significance <0.05. Based on the determination coefficient value (R²) also states that the test results of customer experience variables and service quality simultaneously have an effect of 0.960 or 96%, while the remaining 4% is influenced by other variables not involved in this study.